2008
DOI: 10.1177/1069072708317367
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Interpreting Career Decision-Making Difficulties

Abstract: This research develops and tests a procedure for interpreting individuals' responses in multiscale career assessments, using the Career Decision-Making Difficulties Questionnaire (CDDQ). In Study 1, criteria for ascertaining the credibility of responses were developed, based on the judgments of 39 career-counseling experts. In Study 2, the proposed estimate of the responses' differentiation was validated, using the judgments of 140 experts. In Study 3, the procedure for assessing the relative salience of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 36 publications
2
62
0
3
Order By: Relevance
“…Are they reliable and trustworthy?" In the case of assessing individuals' career decision-making difficulties, these questions have led to the development of a systematic four-step procedure (Amir, Gati, & Kleiman, 2008) that was tested and validated with career counselors' expert judgments:…”
Section: Integrating Theory and Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Are they reliable and trustworthy?" In the case of assessing individuals' career decision-making difficulties, these questions have led to the development of a systematic four-step procedure (Amir, Gati, & Kleiman, 2008) that was tested and validated with career counselors' expert judgments:…”
Section: Integrating Theory and Researchmentioning
confidence: 99%
“…These groups can then be compared to find their similarities and differences in the assessments used (e.g., Willner, Gati, & Guan, 2015). Also, experts' knowledge can be translated into structured interventions (e.g., dealing with dysfunctional career thoughts found in the CTI responses [Sampson et al, 1998] and providing recommendations for dealing with specific career decision-making difficulties that emerged in the CDDQ [Amir, Gati, & Kleiman, 2008]). However, theory-based ICT interventions should always be tested for empirical validity as well as practical effectiveness (e.g., which types of difficulties can be reduced by what interventions to which individuals), and the conclusions can and should be used to upgrade interventions and refine the theory.…”
Section: The Challenges Of Integrating Theory Research and Practicementioning
confidence: 99%
“…These criteria were based on theoretical considerations and validated using the judgments of career counseling experts (for details see Amir et al, 2008).…”
Section: The Procedures Of Interpretationmentioning
confidence: 99%
“…As reported by Amir et al (2008), career counselors suggested adding reservations to the feedback if there are one or two reasons for them. However, if all three indicators reflect questionable interpretability, no feedback about the specific focuses of the client's career decision-making difficulties should be provided.…”
Section: The Procedures Of Interpretationmentioning
confidence: 99%
“…En este mismo sentido otros autores (Amir, Gati y Kleiman, 2008;González Maura, 2006;Uribarri, 2004) detallan también factores o condicionantes, tanto personales como sociales, que influyen en la conducta vocacional y recogen la relación existente entre ellos.…”
Section: Introductionunclassified